Inhibition of CAL27 Oral Squamous Carcinoma Cell by Targeting Hedgehog Pathway With Vismodegib or Itraconazole - Freitas, Raíza Dias (Front Oncol, 2020)
Oral Squamous Cell Carcinoma (OSCC) presents an important challenge for the health systems worldwide. Thus, unraveling the biological mechanisms involved in OSCC pathogenesis is essential to the discovery of new drugs with anticancer potential. The Hedgehog (HH) pathway has shown promising results as a therapeutic target both in vitro and in vivo. This study aimed to investigate the effects of vismodegib and itraconazole on the expression of Hedgehog (HH) genes (PTCH1, SMO, and GLI1), cell cycle and cell death in OSCC cells. Alamar Blue assay was used to assess the cytotoxicity of vismodegib and itraconazole in a panel of oral cancer cell lines, including CAL27. The expression of HH signaling components after treatment with vismodegib and itraconazole, at concentrations of 25 or 50 μg/ml was evaluated by qPCR. Cell cycle and apoptosis were evaluated by flow cytometry after 72 h treatment with 50 μg/ml of vismodegib or itraconazole. HH signaling was activated in OSCC cell lines CAL27, SCC4, SCC9, and HSC3. Vismodegib and itraconazole significantly reduced CAL27 cell viability after 48 h of treatment. Gene expression of PTCH1, SMO, and GLI1 decreased in response to 24 h of treatment with vismodegib or itraconazole. Furthermore, CAL27 cells exhibited alterations in morphology, cell size, and cellular granularity. An increase in the DNA fragmentation was observed after treatment and both inhibitors induced apoptosis after 72 h. In conclusion, SMO inhibitors vismodegib and itraconazole demonstrably reduced the expression of HH genes in CAL27 OSCC cell line. In addition, treatment with vismodegib and itraconazole reduced cellular viability and altered the morphology of CAL27 cells, and also induced apoptosis.